Immunomodulatory actions of vitamin D in various immune-related disorders: a comprehensive review - Ghaseminejad-Raeini, Amirhossein; Ghaderi, Ali; Sharafi, Amirmohammad; Nematollahi-Sani, Behrad; Moossavi, Maryam; Derakhshani, Afshin; Sarab, Gholamreza Anani (Frontiers in Immunology, 2023)
Since many years ago, vitamin D has been acknowledged for its role in maintaining calcium and phosphate balance. However, in recent years, research have assessed the immunomodulatory role and come up with conflicting conclusions. Because the vitamin D receptor is expressed in a variety of immune cell types, study into the precise role of this molecule in diseases, notably autoimmune disorders, has been made possible. The physiologically activated version of vitamin D also promotes a tolerogenic immunological condition in addition to modulating innate and acquired immune cell responses. According to a number of recent research, this important micronutrient plays a complex role in numerous biochemical pathways in the immune system and disorders that are associated. Research in this field is still relatively new, and some surveys claim that patients with severe autoimmune illnesses frequently have vitamin D deficiencies or insufficiencies. This review seeks to clarify the most recent research on vitamin D's immune system-related role, including the pathophysiology of major disorders.